'Never infuriate a creature that bleeds for successive seven days': (un)supportive discourses of Chinese male netizens on dysmenorrhea. Issue 1 (2nd January 2023) - Yang, Xinying; Qiu, Hongfeng; Zhu, Ranran
ABSTRACT: On Zhihu, China's biggest social network platform for knowledge sharing, young male users are invited to put forward their experiences and suggestions on how to alleviate their partner's menstrual pain. By means of thematic analysis and critical discourse analysis, this present study concentrates on the (un)supportive discourses of male netizens on dysmenorrhea and their implying gender ideologies. It finds out that Chinese young men to a certain extent have broken the restraint of traditional gender norms by offering tangible, emotional, and informational support for their partners. However, this kind of idealized male tenderness is still embedded in the problematic gender relations, and is a form of gender performativity informed by consumerism, neoliberalism, and the Confucian tradition. Moreover, a few discourses featuring male levity and misogyny indicate the dual nature of knowledge-sharing social networks, which imbue hidden gender issues with visibilities on the one hand and reproduce gender inequity on the other.